2013
DOI: 10.3748/wjg.v19.i47.8831
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical and selective roles of galectins in hepatocarcinogenesis, liver fibrosis and inflammation of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) represents a global health problem. Infections with hepatitis B or C virus, non-alcoholic steatohepatitis disease, alcohol abuse, or dietary exposure to aflatoxin are the major risk factors to the development of this tumor. Regardless of the carcinogenic insult, HCC usually develops in a context of cirrhosis due to chronic inflammation and advanced fibrosis. Galectins are a family of evolutionarily-conserved proteins defined by at least one carbohydrate recognition domain with af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 183 publications
0
61
0
1
Order By: Relevance
“…The endogenous lectin Gal1 is mainly known for its regulatory role in the regulation of immune cell programs, inflammatory responses and angiogenesis; however it has also been implicated in the control of cell survival, signaling and proliferation, acting in different model systems either as a mitogen or as an inhibitor of cell proliferation [1, 11]. Here we identified a novel role for Gal1 in LR following PHx.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The endogenous lectin Gal1 is mainly known for its regulatory role in the regulation of immune cell programs, inflammatory responses and angiogenesis; however it has also been implicated in the control of cell survival, signaling and proliferation, acting in different model systems either as a mitogen or as an inhibitor of cell proliferation [1, 11]. Here we identified a novel role for Gal1 in LR following PHx.…”
Section: Discussionmentioning
confidence: 80%
“…Expression of Gal1 is associated with the aggressiveness of hepatocellular carcinoma (HCC) in mice [11], low survival of HCC patients [12], and poor prognosis in HCC following resection [13]. Interestingly, Gal1 acts by promoting HCC cell adhesion through PI3K and/or ERK1/2 signaling pathways [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lectin interactions with endogenous glycans control cell signaling and neovascularization [96, 203] and, therefore, can provide important information about hypoxic environments. When performing in vitro studies, Croci and Rabinovich (2014) observed that serum-free conditioned medium from an anti-VEGF refractory, but not anti-VEGF sensitive tumors, induced endothelial cell exposure of Gal-1-specific ligands.…”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%
“…Most often, these di-saccharides are part of complex glycans carried by glycoproteins or glycolipids (1). The domains of galectins that directly interact with carbohydrate ligands are carbohydrate recognition domains (CRD) 4 (2). The CRDs are made of about 135 amino acids forming a groove in which the carbohydrate ligand can bind.…”
mentioning
confidence: 99%